Problem-Based Learning in Remote Learning Scenario Utilizing Climate Change Virtual Reality Video in Mobile Application to Train Critical Thinking - Aliyu, Hassan; Ebikabowei, Musah; Kola, Aina Jacob (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
The imperative to address climate change in educational curricula stems from its profound implications for the sustainability of human life. A crucial aspect of this education is fostering critical thinking (CT) in students, as they form their perspectives on climate change. Traditional teaching approaches alone have proven inadequate in developing students' CT concerning this complex issue, particularly when learning remotely. To address this challenge, students must be actively engaged with the realities of climate change. In response to this need, the current study aimed to apply the problem-based learning (PBL) in remote learning scenario utilizing climate change virtual reality (VR) video in mobile application to train students’ CT skills. Utilizing a mixed method approach, the study involved 86 high school students, divided evenly between experimental and control groups, using a 'true experimental design' to quantify CT skill improvements. Complementing the quantitative data, the study also conducted semi-structured interviews with teachers participating in the interventions, providing valuable insights into their responses to the learning methods. The instruments used to measure students' CT skills were carefully validated for psychometric properties (validity and reliability). The study's overall findings indicate that the PBL approach integrated with climate change VR videos in mobile applications effectively enhances students' critical thinking skills, surpassing the outcomes of traditional teaching methods. Moreover, the feedback received from teachers who took part in the teaching interventions was overwhelmingly positive, reinforcing the efficacy of the learning approach. This research highlights the significance of implementing PBL and VR experiences to cultivate CT among students, particularly in the context of climate change education.